2010
DOI: 10.1136/oem.2009.053645
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of regional pain and associated disability in Japanese workers

Abstract: Objectives-To assess the prevalence and correlates of regional pain and associated disability in four groups of Japanese workers.Methods-As part of a large international survey of musculoskeletal symptoms (the CUPID study), samples of nurses, office workers, sales/marketing personnel and transportation operatives in Japan completed a self-administered questionnaire (response rate 83%). The questionnaire covered experience of pain in six anatomical regions, associated disability and sickness absence, and variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
76
4
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(98 citation statements)
references
References 29 publications
9
76
4
9
Order By: Relevance
“…Some recent studies show interesting results. For example, a cross-sectional study in Japan and the UK found that large differences exist between the countries in wrist or hand pain and sickness absence due to musculoskeletal pain (23). A cross-sectional study in India and the UK found that cultural factors, such as health beliefs and expectations, may have and important influence on musculoskeletal symptoms (24).…”
Section: Discussionmentioning
confidence: 99%
“…Some recent studies show interesting results. For example, a cross-sectional study in Japan and the UK found that large differences exist between the countries in wrist or hand pain and sickness absence due to musculoskeletal pain (23). A cross-sectional study in India and the UK found that cultural factors, such as health beliefs and expectations, may have and important influence on musculoskeletal symptoms (24).…”
Section: Discussionmentioning
confidence: 99%
“…have been cross-sectional in design [13,43,[48][49][50][51][52][53][54][55], and these have found relative risks or odds ratios of up to 4-5 for pain at specific anatomical sites. Moreover, the relationship extends to widespread pain [56], and there are indications that relative risks are even higher for pain occurring at multiple sites [10,12].…”
Section: Methods Of Assessmentmentioning
confidence: 99%
“…Importantly, the relationship is not only with awareness and reporting of musculoskeletal symptoms, but also with disability for everyday activities as a consequence of musculoskeletal pain [10,[12][13][14]49].…”
Section: Methods Of Assessmentmentioning
confidence: 99%
See 2 more Smart Citations